Spectral proof for the 4-aminophenyl disulfide plasma assisted catalytic reaction - Lixin Xia (Nature Portfolio, 2017)
Abstract 4-Aminophenyl disulfide (APDS) forms on the surface of silver nanoparticles due to chemical adsorption and disulfide bond breakage. This leads to the formation of new silver chemical bonds to result in the new compound NH2-C6H6-S-Ag. This novel material produces enhanced Raman spectra under weak laser light irradiation. When irradiated a plasma-assisted catalytic coupling reaction of NH2-C6H6-S-Ag occurs leading to the formation of 4,4-dimercaptoazobenzene (DMAB). Raman spectroscopy was used to monitor this reaction process, showing clear spectral changes associated with each step after addition of Ag nanoparticles onto the APDS powder. This method clearly shows the mechanism of the plasma-assisted catalytic reaction and may also be useful for spectral imaging purposes.